EFEKTIVITAS AIR REBUSAN DAUN BINAHONG (ANREDERA CORDIFOLIA) TERHADAP FLOUR ALBUS PADA REMAJA - Maharani Hayuningtyas, Cinthya; Rosyida; Tetty Rihardini; Anik Latifah (Jurnal Medicare, 2025)
Fluor albus remains a common reproductive health problem among adolescent girls. It is characterized by excessive vaginal discharge excluding blood with variations in odor, consistency, and color. If not managed properly, this condition can cause discomfort and potentially disrupt reproductive organ function. This study aimed to evaluate the effectiveness of boiled Binahong leaf water in reducing fluor albus among adolescents. A pre-experimental design with a one-group pretest-posttest method was used. The population included all female students from SMAS Nurusshaleh and MTS Nurusshaleh in Bangkalan Regency who experienced pathological fluor albus, with a sample of 30 students selected through total sampling. The intervention involved using boiled Binahong leaf water for perineal cleansing twice daily over five consecutive days.. Results showed that all participants (100%) experienced abnormal fluor albus before the intervention, while 29 participants (96.7%) improved to normal conditions afterward. The Wilcoxon test revealed a significant value of p = 0.000 (< 0.05), indicating a statistically significant difference before and after the intervention. In conclusion, boiled Binahong leaf water is effective in reducing fluor albus among adolescents and can be considered a safe, accessible traditional treatment option.